2003
DOI: 10.1007/s00259-002-1020-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic lymph flow imaging in patients with oedema of the lower limb for evaluation of the functional outcome after autologous lymph vessel transplantation: an 8-year follow-up study

Abstract: The purpose of this study was to monitor the functional outcome of microsurgical intervention on lymph drainage by means of non-invasive, readily available lymphoscintigraphy. Eight patients with primary or secondary lymphoedema of the lower limb were investigated before and for 8 years after autologous lymph vessel transplantation. For scintigraphy, technetium-99m labelled nanocolloid was subcutaneously injected into the first interdigital space of the affected limb. Sequential images were acquired up to 6 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 13 publications
0
31
0
6
Order By: Relevance
“…LS is currently the primary imaging modality to investigate peripheral lymphedema [3,16]. The delay in ascent of the tracer is considered the major diagnostic indicator of impaired lymphatic transport.…”
Section: Discussionmentioning
confidence: 99%
“…LS is currently the primary imaging modality to investigate peripheral lymphedema [3,16]. The delay in ascent of the tracer is considered the major diagnostic indicator of impaired lymphatic transport.…”
Section: Discussionmentioning
confidence: 99%
“…Another surgical procedure of lymphoedema with previous lymphoscintigraphic diagnosing and subsequent lymphoscintigraphic follow up, consists in autologous lymph vessel transplantation [25]. The authors concluded that lymphoscintigraphy is helpful not only in planning microsurgical treatment but also in monitoring the postoperative outcome that they performed for 8 years.…”
Section: Main Applications Of Lymphoscintigraphy In Lymphoedemamentioning
confidence: 98%
“…Fehlbefunde k ö nnen durch Vermeidung einer intravasalen Applikation des Radiopharmakons verhindert werden [8,15,24,26,27,30,31,46,48] . Zudem kann als Therapiekontrolle ü ber viele Jahre hinweg eine persistierende Funktion der Lymphgef ä ß transplantate durch die lymphszintigrafi sche Bildgebung im Vergleich zum pr ä operativen Zustand dokumentiert werden [5,42,43] . Bei einer ü ber die Beurteilung mittels Transportindex hinausgehende Quantifi zierung des Lymphabtransportes mittels Regions-of-Interest, muss bei klinischen Untersuchungen ber ü cksichtigt werden, dass hierbei die Ergebnisse stark von der w ä hrend des Untersuchungszeitraumes ausge ü bten Muskelanstrengung seitens des Patienten abh ä ngen; letztere m ü ssen daher streng standardisiert werden.…”
Section: Diskussion and Lymphogener Transportunclassified